Methane Production of Full-Scale Anaerobic Digestion Plants Calculated from Substrate’s Biomethane Potentials Compares Well with the One Measured On-Site - Holliger, Christof; Fruteau de Laclos, Hélène; Hack, Gabrielle (Frontiers in Energy Research, 2017)
Biomethane potential (BMP) tests are used to determine the amount of methane that can be produced from organic materials in order to design different components of full-scale anaerobic digestion plants such as size of the digesters and units exploiting the produced biogas. However, little is known on how well BMPs compare with biogas production from the same organic materials in full-scale installations. In this study, two anaerobic digestion plants were chosen to carry out such comparisons, a dry anaerobic digestion (AD) plant treating green waste from urban areas and food waste from restaurants and supermarkets, and a liquid AD plant treating waste sludge from wastewater treatment and seven additional organic wastes. The BMPs of multiple samples of the individual organic materials collected during a period of seven to nine months were determined. Separate tests of mixtures of organic materials confirmed that the BMP of the mixtures can be calculated by adding the BMPs of the individual materials. The weekly methane production during the investigated periods was calculated from the full-scale installation data on the feeding of the digesters and the BMP’s of each substrate fed into the digesters and compared with the weekly methane production measured on-site. The latter was calculated from the most accurately measured entity, either the electricity or the volume of purified biomethane injected into the grid. The weekly methane production rates calculated from BMPs and the one measured on-site were very similar and followed the same pattern. Some exceptions could be explained by e.g. an overload of the full-scale installation. The measured weekly methane production accounted for 94.0±6.8% and 89.3±5.7% of the calculated weekly methane production for the wet and dry AD plant, respectively. For 26 out of 29 weeks, the calculated weekly methane production overestimated the measured one in the case of the wet AD plant and for 37 out of 39 weeks for the dry AD plant. Based on these results, it is proposed using an extrapolation coefficient of 0.8 to 0.9 to estimate the methane production of full-scale AD plants from BMPs of the substrates to be digested and their specific organic loads.